(untitled) (Acta Scientiarum. Health Sciences, 2022)
Systemic sclerosis (SSc) is a systemic autoimmune disease of the connective tissue with unknown etiology, characterized by abnormal collagen deposition in the skin. The changes in patients result in the obliteration of microvessels and fibrosis, leading to damage to the skin, gastrointestinal tract, kidneys, lungs, heart, and oral cavity. Brazil has insufficient data about the epidemiological and laboratory aspects of SSc. This study aimed to identify and characterize the patients in treatment for SSc in Cascavel/PR, a city in the south of Brazil. Data were collected from March 2019 to September 2020 from all health services of Cascavel that provide care in rheumatology: a university-affiliated hospital, two public outpatient clinics, and six private clinics. Data about age, sex, residence, time to diagnosis, the form of the disease, and the results of tests for antinuclear (ANA) and anti-extractable nuclear antigens (ENA) antibodies were obtained. The study identified 57 patients; 82.5% were female with a mean age of 50.4 years, and the predominant disease form was diffuse (52.6%). The ANA test was positive in 87.7% of the patients, of which 49.2% showed high titers and a predominance of the centromeric pattern. Anti-Scl-70, anti-centromere (ACA), and anti-RNA polymerase III antibodies were positive in 28.1%, 25%, and 5% of the patients. The characteristics of the patients diagnosed with SSc in Cascavel/PR are similar to those reported in the literature. This study contributed to the scarce Brazilian data about the disease.